2016
DOI: 10.1534/g3.116.028746
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution SNP Array-Based Linkage Map Anchors a New Domestic Cat Draft Genome Assembly and Provides Detailed Patterns of Recombination

Abstract: High-resolution genetic and physical maps are invaluable tools for building accurate genome assemblies, and interpreting results of genome-wide association studies (GWAS). Previous genetic and physical maps anchored good quality draft assemblies of the domestic cat genome, enabling the discovery of numerous genes underlying hereditary disease and phenotypes of interest to the biomedical science and breeding communities. However, these maps lacked sufficient marker density to order thousands of shorter scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 64 publications
(105 reference statements)
0
70
0
Order By: Relevance
“…; Li et al . ). Finally, reduced recombination has been observed across several Mb sections of multiple chromosomes in collared flycatchers (Burri et al .…”
Section: Example References From Lowry Et Al () Table S1 Of Genome Smentioning
confidence: 97%
See 2 more Smart Citations
“…; Li et al . ). Finally, reduced recombination has been observed across several Mb sections of multiple chromosomes in collared flycatchers (Burri et al .…”
Section: Example References From Lowry Et Al () Table S1 Of Genome Smentioning
confidence: 97%
“…Recombination deserts spanning 50 Mb have been observed in cats (Li et al . ); 34 Mb recombination deserts have been found in pigs (Ai et al . ; Li et al .…”
Section: Example References From Lowry Et Al () Table S1 Of Genome Smentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed several panels of cat-rodent somatic cell hybrids and began mapping the cat genome (18). We built a linkage map with a breeding pedigree between house cats and a related species, leopard cats (Prionailurus bengalensis), developed at the NIH Animal Breeding facility in Poolesville, Maryland (19). This was exciting to me and sparked a career-long fascination (indeed, obsession) with the biology, evolutionary genetics, and medicine of cats (20)(21)(22)(23).…”
Section: Originsmentioning
confidence: 99%
“…To more thoroughly understand the interplay between local recombination rates, inferred interspecies gene flow and phylogenomic resolution in the cat family, we analyzed the distribution of phylogenetic signal across the genomes of 27 felid species in the context of recombination rates inferred from high-resolution linkage maps for the domestic cat (Menotti-Raymond et al 1999;Menotti-Raymond et al 2003;Li, Hillier, et al 2016). We found that phylogenomic signal is strongly influenced by ancient admixture, that it is partitioned within the nuclear genome by local recombination rates, and that the inferred species branching events are enriched on the X chromosome.…”
Section: Introductionmentioning
confidence: 99%